Prevalence, awareness, treatment, and control of hypertension in southwestern China - Huang, Xiao-Bo; Zhang, Yang; Wang, Tzung-Dau; Liu, Jian-Xiong; Yi, Yan-Jing; Liu, Ya; Xu, Rong-Hua; Hu, Yong-Mei; Chen, Mao (Scientific reports, 2019)
This study investigated the prevalence, awareness, treatment, and control of hypertension and associated factors among urban adults in southwestern China. The study was conducted from 2013–2014 and used a multistage cluster sampling method to select a representative sample of 11,517 people in southwestern China, aged 35–79 years. Hypertension was defined as either systolic blood pressure of 140 mmHg or greater, diastolic blood pressure of 90 mm Hg or greater, or self-reported current treatment for hypertension with antihypertensive medications. In the study population, hypertension prevalence was found to be 38.4%, with rates of 40.0% and 37.5% for men and women, respectively ( p = 0.03). Hypertension prevalence increased with age in both men and women (trend p both <0.01). Among hypertensive patients, 47.9% were aware of their hypertension, 40.1% were undergoing antihypertensive treatment, and 10.3% achieved BP control. A multiple-factor analysis revealed that age, male gender, low educational achievement, family history of hypertension, overweight or obesity, abdominal obesity, and hypertriglyceridemia were positively related to hypertension, while physical exercise was negatively related to hypertension. The prevalence of hypertension among urban adults aged 35 to 79 years in southwestern China was high, while levels of awareness, treatment, and control of hypertension were low. Multifaceted interventional measures are needed to solve the unmet needs.